(untitled) (European Journal of Health Research, 2020)
Despite growing interest in high-intensity interval training as a time-effective way for older adults to improve their health, there is little consensus regarding the better way to plan a HIIT intervention. Given the loss of function and health problems of an older adult population, the identification and characterization of interventions and strategies is a fundamental prerequisite. The goals of this review are examining high-intensity interval training as a way to improve health, and finding out the highestintensity viable HIIT protocol. Studies were included in this systematic review if: (1) they studied a population of older adults; (2) prescribed an intervention that can be described as high intensity; and (3) reported health-related outcome measures. The resulting 14 papers were included in our study. The present review found that high-intensity interval training is an effective tool to improve indicators of body composition as well as cardiometabolic and cardiovascular health, with 90-95% HRmax cycle ergometer sessions held two-three times a week, with a minimum session length of 40 minutes, in an intervention at least 12-week long, effecting significant improvements on the health of participants. Recommendations regarding optimal exercise duration and rest intervals must remain ambiguous given the scarcity of published literature and the methodology and limitations of those studies that are already available